Self-rated joint hypermobility: the five-part questionnaire evaluated in a Swedish non-clinical adult population - Martin Glans; Mats B. Humble; Marie Elwin; Susanne Bejerot (BMC Musculoskeletal Disorders, 2020)
Abstract Background The conventional way to identify generalised joint hypermobility is by a physical examination according to the Beighton Score. However, a physical examination is time-consuming in clinical practise and may be unfeasible in population-based studies. The self-assessment five-part questionnaire on hypermobility (5PQ) offers a more practicable way to identify GJH. The aim of this study was to test validity and reliability of the five-part questionnaire on hypermobility (5PQ) translated into Swedish on a non-clinical adult population. Methods A structured procedure was used for the translation of the 5PQ into Swedish. The Beighton Score was used as reference standard for generalised joint hypermobility. Test-retest reliability was tested in a separate group who filled in the questionnaire twice with a ten-week interval. Participants consisted of a convenience sample recruited in Stockholm, Sweden (2017). Results A total of 328 participants were included in the study, 297 participants in the validity group and 31 participants in the reliability group. When evaluated against a present Beighton Score with an age-dependent cut-off, the Swedish 5PQ attained a sensitivity of 91%, a specificity of 75% and an area under the curve of 0.87. The Swedish 5PQ showed substantial to almost perfect test-retest reliability. Conclusions The Swedish 5PQ is a valid and reliable instrument to screen for or to identify generalised joint hypermobility.